Leviathans : multinational corporations and the new global history - Chandler, Alfred D. (Cambridge, 2005)
Introduction / Alfred Chandler and Bruce Mazlish -- The Scope of the Multinational Phenomenon -- A primer on multinational corporations / Brian Roach -- Multinational enterprise to 1930: discontinuities and continuities / Mira Wilkins -- Multinationals from the 1930s to the 1980s / Geoffrey Jones -- Innovative multinational forms: Japan as a case study / Sei Yonekura and Sara McKinney -- Cultural and Social Implications of Multinationals -- The social impacts of multinational corporations: an outline of the issues, with a focus on workers / Neva R. Goodwin -- A global elite? / Bruce Mazlish and Elliott Morss -- The Governance of Multinationals -- Governing the multinational enterprise: emergence of the global shareowner / Robert A. G. Monks -- The financial revolutions of the twentieth century / Zhu Jia-Ming and Elliott R. Morss -- Multinational corporations, the protest movement, and the future of global governance / Stephen J. Kobrin -- Conclusion / Bruce Mazlish.